Bovine nucleus pulposus decellularization using freeze drying technique to form a biological scaffold - Romaniyanto; Prijosedjati, Raden Andhi; Ermawan, Rieva; Hakim, Fikar Arsyad; Saddalqous (Surgical Residency Program Syiah Kuala University, 2024)
Introduction: As much as 40% of low back pain patients are caused by degenerative disc disease. The current treatments are fusion stabilization and total disc replacement, which have a risk for adjacent segment disease. These suboptimal results have become the beginning of the development of regenerative therapy. The success of this therapy will increase if the scaffold meets the ideal conditions. Biological scaffolds provide a cell growth environment that resembles the original tissue. Bovine intervertebral nucleus pulposus can become promising scaffolds. Objective: This research describes the proper freeze-drying approach for decellularizing bovine nucleus pulposus to create a biological scaffold. Methods: We conducted an experimental post-test control design study using bovine coccygeal nucleus pulposus material. All treatment groups underwent freeze-drying with Buchi Lyovapor™ L-200/L-200 Pro. All groups were evaluated for the level of decellularization using the Quick-DNA™ Miniprep Plus Kit (Zymo Research®) and remaining glycosaminoglycan levels by Alcian Blue staining. Results: Comparison of DNA concentrations obtained p-values respectively <0.0001 (p <0.05), which means that all the treatments showed a decrease in DNA concentration compared to the control group. The comparison of the glycosaminoglycan percentage between the P1 vs. Control group obtained a value of p=0.381 (p>0.05), which means that the glycosaminoglycan percentage results for the P1 group were not significantly different from the control group. Conclusion: This study of group P1 showed that decellularization of the bovine nucleus pulposus by freeze-drying technique can form an excellent biological scaffold.